Globalisation and Its Impact on Economic : A Review - Namita (Innovative Research Thoughts, 2017)
In response to the challenges of globalization, many universities have adopted the strategy of “internationalizing the curriculum” for developing leaders that drive global problem solving with all stakeholders, rather than “simply” training skilled professionals for business. This chapter presents a case study about internationalization and introduction of an innovative curriculum in “Global Logistics” at a business school in a Historically Black College and University (HBCU) in the State of Georgia, United States. In order to provide students with a complete global experience for employment in the global economy, the business school introduced a new program with emphasis on Logistics and Supply Chain Management (SCM), and International Business Environment called “Global Logistics and International Business (G-LIB).” In this chapter, we discuss the need of having an international business logistics program at a HBCU and discuss its implications for faculty, students, and businesses